2017
DOI: 10.4047/jap.2017.9.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Metal stain on monolithic zirconia restoration: A case report

Abstract: In restorative treatment using fixed dental prostheses, dentists should select appropriate restoration material among various types of dental materials. The strength, marginal fit, esthetics, wear resistance, biocompatibility, and cost are important factors in the choice of restoration materials. The present case showed a surface stain on a monolithic zirconia restoration that was due to wear between the monolithic zirconia restoration and the base metal alloy restoration. This phenomenon was confirmed by surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…However, the clinical outcomes of monolithic zirconia restorations remain inadequately studied. Therefore, the long‐term prognosis of monolithic zirconia remains unknown .…”
mentioning
confidence: 99%
“…However, the clinical outcomes of monolithic zirconia restorations remain inadequately studied. Therefore, the long‐term prognosis of monolithic zirconia remains unknown .…”
mentioning
confidence: 99%
“…[36] However 'full contour' zirconia based restorations without a porcelain layer have been shown to be problematic in some cases with wear of the opposing teeth causing gross fracture and ultimate total failure of the prosthesis. [26,37] In a study by Park et al, wear resistance of the 3D printed resin material was compared to the milled and the conventional self-cured resin materials opposing zirconia and metal antagonists (CoCr alloy). [38] The basic component of all the three resin materials was similar but the study found differences in wear patterns between the materials and the casted cobalt-chromium (CoCr) alloy denture abraders.…”
Section: Iv) Peek and Nylonmentioning
confidence: 99%
“…Furthermore, a number of PMMA dental models can be easily fabricated, polished, and repaired using the 3D printers, which not only reduces the production time but also allows multiple 3D copies to be produced without altering the dental anatomy. [36,37,38] However, as the studies above have shown, the flexural strength of PMMA decreases gradually over time, meaning current formulations may be inadequate for use as long term restorations. Studies have reported that the use of PMMA resin materials in dental restoration cause irritation of oral tissues, have low wear resistance, and high volume shrinkage due to leaching of the free monomer.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the possibility of an excessive wear of dental alloys by zirconia was suggested. 22 For these reasons, we conducted an in vitro study 23 on the wear of three dental alloys against 3Y-TZP monolithic zirconia. It was shown that the wear of metal alloy differs according to the alloy type (the antagonist specimen) and the surface roughness of zirconia (the substrate specimen).…”
Section: Introductionmentioning
confidence: 99%